If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 68 + -2x = 9x + 24 Reorder the terms: 68 + -2x = 24 + 9x Solving 68 + -2x = 24 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 68 + -2x + -9x = 24 + 9x + -9x Combine like terms: -2x + -9x = -11x 68 + -11x = 24 + 9x + -9x Combine like terms: 9x + -9x = 0 68 + -11x = 24 + 0 68 + -11x = 24 Add '-68' to each side of the equation. 68 + -68 + -11x = 24 + -68 Combine like terms: 68 + -68 = 0 0 + -11x = 24 + -68 -11x = 24 + -68 Combine like terms: 24 + -68 = -44 -11x = -44 Divide each side by '-11'. x = 4 Simplifying x = 4
| 18-4x=38 | | -34-7a=-8(6a-6) | | 4x^2-27x=0 | | -5(v+8)+4=-35-6v | | -2m-5m=-14 | | -5b+4b=1 | | 14(4n+6)=-7(7n+19) | | -10x=-9 | | -4=-2n+6n | | -5=4r+r | | 26.54-p=0.5(50-p) | | 4(-2+6x)=-6-(2-8x) | | -9(10x+10)=9(-1-11x) | | 6x+10=100-4x | | X+6(x+4)=7x-22 | | 7r=-56 | | 7k-18=-6(2-k) | | 4(5-y)=8(3-y) | | -4n=-24 | | x-4x=0 | | -10=-5n-4+6n | | -3=-p+2p | | 1+3x=17+x | | -11=-6+2b+3b | | -9+5m=-39 | | 4b^2-53=11 | | .5(6x+18)=3(x+3) | | 4(2x-3)=44 | | 4x+8=-32 | | 11x+7=10x-8 | | -8(y+9)=-40 | | 8x-4=6x+2 |